Screening of a Soil Tyrosianse Producing Bacterial Strain HM24 and Comparison of its Tyrosinase Activity in Different Mediums Containing Natural Sources of L-tyrosine - Seyed Muhammad Hamid Malekpour; Moj Khaleghi; Alireza Akhtarpour (Journal of Genetic Resources)
Tyrosinases are essential enzymes with diverse applications, such as breaking down phenolic compounds and producing melanin. Actinobacteria are one of the most notable tyrosinase producers. This study investigated tyrosinase-producing actinobacterial strains and evaluated enzyme activity in different sources of L-tyrosine. Twenty strains were isolated from the soil of Langar, Kerman, Iran, with characteristics of actinobacteria (gram-positive filamentous or rod-shaped bacteria and powdery consistency colonies that stick firmly to agar surface). All strains were cultured in a medium with L-tyrosine to assess tyrosinase production. The best tyrosinase-producing strain was selected based on dark-colored colony formation. Also, enzyme activity was evaluated in the four mediums with different L-tyrosine sources (Tyrosine, Glucose-Yeast-Peptone (GYP), Soybean, and Peanut). On the other, the pigment produced by actinobacteria was investigated for significant properties such as Sun Protection Factor (SPF) and antioxidant activity. The results showed that the HM24 strain is the best strain for producing tyrosinase. The results showed that the HM24 strain was the best tyrosinase-producing strain, and the most enzyme activity was in the peanut medium as well as in the soybean meal substrate. According to the 16S rRNA sequencing, the HM24 strain belonged to the genus Microbacterium with 99.97% identity. The pigment produced by HM24 demonstrated an SPF of 134.36 and a 69% DPPH reduction, which indicated strong antioxidant activity. These findings underscore the significant potential of actinobacterial strains in various industrial applications. Considering the production of tyrosinase enzyme by strain HM24, its ability to efficiently utilize natural L-tyrosine sources, and the biological properties of the resulting pigment, this strain holds significant potential for applications in various industrial processes.